(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The rapid advancement of technology, such as artificial intelligence (AI) and robotics, has impacted all industries, including education. A recent report from IBM, Burning Glass and Business Higher Education Forum shows that the number of job opportunities for data and analytics skills will increase by 364,000 to 2,720,000 in 2020. That means that the gap between supply and demand of people with AI skills is growing, with one report showing a worldwide base of 300,000 AI professionals, but with millions of opportunities available and this gap is resulting in even higher salaries for those in this field.